Fire and water must live together: a novella - Gabbard, Robert Todd (Kansas State University, 2018)
By the year 2037, climate change has destabilized the world’s ecology, politics, and culture. Hawaii has seceded from the United States, instituting the Cultural Reaffirmation, which champions a sustainable, traditional way of life. Eenie is an astronomer on the Big Island of Hawaii. In order to keep the observatory on Mauna Kea operational, she must appease the newly independent island nation by reenacting a mythical sled race between Poliahu, the Hawaiian snow goddess of Maunakea, and Pele, the fierce goddess of lava, personified by a rival geoscientist from Maunaloa’s volcanic laboratory. Once an Olympic contender in the women’s luge, Eenie has won this race twice before. This year, though, the greenhouse effect has caught up with her; there is no snow on Maunakea. Without it, she cannot prevail, and if she doesn’t, the priests of Hawaii’s Cultural Reaffirmation will pull the telescopes down from their most sacred mountain. Eenie struggles against nature’s increasing wrath, gods, monsters, pigs, and political rivals, though her biggest struggle is within herself. Fire and water must live together takes place in an ecodystopic future, though its story pulls from Hawaiian myth. The story’s projection into the future is based on current events, including the Hawaiian sovereignty movement, climate change science, and technology. An accompanying essay frames the novella through three critical lenses: ecocriticism, eco-politics, and post-colonial hybridity. The essay includes a focused look at the setting of Hawaii as it stands today in terms of environment, politics, and people.
Keywords: Political instabilityNear future climate fiction; Hawaiian mythology; Climate change